Effect of viscous dissipation and thermoporesis on the flow over an exponentially stretching sheet - Srinivasacharya, D.; Jagadeeshwar, P. (Zielona Góra: Uniwersytet Zielonogórski)
This article analyses the influence of viscous dissipation and thermoporesis effects on the viscous fluid flow over a porous sheet stretching exponentially by applying convective boundary condition. The numerical solutions to the governing equations are evaluated using a local similarity and non-similarity approach along with a successive linearisation procedure and Chebyshev collocation method. The influence of the pertinent parameters on the physical quantities are displayed through graphs.
Keywords: thermophoresis; viscous dissipation; Eckert number